(untitled) (Training and Practice : Journal of Educational Sciences, 2013)
The aim of this paper is to present the most important concepts and possible interpretations of criminal pedagogy and criminal andragogy. I demonstrate the two different, well-discernible trends of defining the goal of education in prisons. I present the objectives of education in prisons and the actual training process in detail, covering the basic areas, methods and range of educational procedures. Finally, I highlight the aspect that makes the prison a total institution and the impact it has on prisoners.